Nuevos registros herpetofaunísticos para el municipio de Tezontepec de Aldama, Hidalgo, México - Valdez-Rentería, Sharon Yedid; Fernández-Badillo, Leonardo (Instituto de Ecología, A.C., 2016)
This work presents six new records of herpetozoans for the municipality of Tezontepec de Aldama, Hidalgo.